Effect of a quality-improving codend on size selectivity and catch patterns of cod in bottom trawl fishery - Brinkhof, Jesse; Herrmann, Bent; Larsen, Roger B.; Veiga-Malta, Tiago (Canadian Journal of Fisheries and Aquatic Sciences, 2019)
Accepted manuscript version. Published version available at https://doi.org/10.1139/cjfas-2018-0402 . Copyright NRC Research Press. A new codend concept developed and tested exhibited significantly improved quality of caught cod ( Gadus morhua ) compared to that of the conventional codend used in the Barents Sea bottom trawl fishery. However, the design of the new quality-improving codend raised concerns about its size selectivity and the possibility that higher retention probability could negatively impact the catch pattern by increasing the proportion of undersized cod. Therefore, the goal of this study was to quantify and compare the size selectivity and catch pattern for cod when deploying respectively the conventional and new quality-improving codend in the Barents Sea bottom trawl fishery. The new quality-improving codend had significantly lower relative size selectivity than the conventional codend, but no significant difference in the catch patterns was detected in the trawl. Further, estimation of the total size selectivity in the trawl revealed that the increased retention of small cod when using the quality-improving codend was minor. Hence, despite the reduced selectivity, the quality-improving codend can be used with low risk of retaining small cod.